Implementation Issues: a 'FRIENDS for life' course in a mainstream secondary school. Issue 3 (2nd July 2016) - Green, Sarah L.; Atkinson, Sarah
Abstract: "FRIENDS for life" is a manualised, 10 week, Cognitive Behavioural Therapy (CBT) based programme designed to be run in school and community settings. The aim of this study was to evaluate the impact of "FRIENDS for life" when implemented in a mainstream secondary school by school staff. Data regarding implementation of the programme were collected and analysed using activity theory. A Single Case Experimental Design was used to monitor the impact of the intervention on the emotional distress and coping strategies of five secondary school participants. The findings suggest that participation in FRIENDS did not result in the hypothesised reductions in emotional distress, or improvement in coping skills. However programme implementation was incomplete. Analysis using activity theory suggested that factors such as lack of time, space for delivery, and experience and training impacted upon implementation and could be further supported by educational psychologists when developing these interventions.